2018
DOI: 10.1161/jaha.118.008637
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab in Female Breast Cancer Patients With Reduced Left Ventricular Ejection Fraction

Abstract: BackgroundTrastuzumab is life‐extending therapy for breast cancer patients overexpressing the human epidermal growth factor receptor 2 (HER2+), but has known cardiotoxic risk. We sought to determine if trastuzumab can be administered to patients with reduced baseline cardiac function at no higher cardiotoxicity risk than in those with normal cardiac function at baseline.Methods and ResultsWe performed a retrospective study of women treated with trastuzumab for human epidermal growth factor receptor 2 breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 40 publications
0
29
0
4
Order By: Relevance
“…26 In addition, a study of patients with breast cancer who were treated with trastuzumab therapy found that a decline in LVEF ≥10% was more frequent in those with normal LVEF at baseline (defined as ≥53%) compared with those with a low baseline LVEF. 27 There was a trend toward a higher likelihood of class 3 membership with older age, black race, and hypertension, and a lower likelihood in those individuals with a history of cardioprotective medication use at baseline. We postulate that we were limited by statistical power in our ability to adequately assess the associations between baseline cardiovascular risk factors and medications and LVEF trajectory class membership.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…26 In addition, a study of patients with breast cancer who were treated with trastuzumab therapy found that a decline in LVEF ≥10% was more frequent in those with normal LVEF at baseline (defined as ≥53%) compared with those with a low baseline LVEF. 27 There was a trend toward a higher likelihood of class 3 membership with older age, black race, and hypertension, and a lower likelihood in those individuals with a history of cardioprotective medication use at baseline. We postulate that we were limited by statistical power in our ability to adequately assess the associations between baseline cardiovascular risk factors and medications and LVEF trajectory class membership.…”
Section: Discussionmentioning
confidence: 89%
“…Another study demonstrated that the mean baseline LVEF was higher in patients with non‐Hodgkin lymphoma who developed an LVEF decline >10% to ≤50% after exposure to doxorubicin compared with those who did not develop cardiotoxicity . In addition, a study of patients with breast cancer who were treated with trastuzumab therapy found that a decline in LVEF ≥10% was more frequent in those with normal LVEF at baseline (defined as ≥53%) compared with those with a low baseline LVEF …”
Section: Discussionmentioning
confidence: 99%
“…Esse resultado foi superior ao estudo de Dores et al 18 , que constataram que 3,3% das pacientes tiveram FEVE abaixo de 55%. Nowsheen et al 19 demonstraram que 73,2% das pacientes que tinham FEVE basal normal e que foram submetidas ao tratamento com trastuzumabe após uso de antraciclinas tiveram uma redução da FEVE em mais de 10%, caracterizando o efeito cumulativo e potencializador desses medicamentos quanto à cardiotoxicidade.…”
Section: Discussionunclassified
“…Patients receiving adjuvant trastuzumab undergo periodic monitoring of LVEF every three months while on therapy (14); those experiencing decline in LVEF ≥ 16% from baseline or LVEF below normal limits and ≥ 10% decline are asked to withhold treatment for at least four weeks and continue LVEF monitoring every four weeks until resolution. Older age (> 50 years) and pre-existing cardiovascular (CV) diseases, such as uncontrolled hypertension and congestive heart failure, have been implicated in increasing the risk of TIC (10,(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%